FAKTOR-FAKTOR PENYEBAB KURANG EFEKTIFNYA IMPLEMENTASI KEBIJAKAN HARGA ECERAN TERTINGGI (HET) PUPUK BERSUBSIDI DI KECAMATAN SUNGAI RAYA KABUPATEN KUBU RAYA - Sugihartini Utami E.01107038 (PublikA, Jurnal Ilmu Administrasi Negara, 2012)
AbstractThis study is conducted to investigate what factors that causes ineffectiveness inimplementation of highest paid retail policy of subsidized fertilizer in KecamatanSungai Raya Kabupaten Kubu Raya. In this research, the researcher used qualitativeresearch. The data was collected through observations in order to get a picture of theobject under study, while the primary data was obtained through an interview whichwas supported by archival investigation, files and documents collection, and otherresources related to the study, and to know the validity of the data the researcher usedtriangulation method. The results showed that the factors that led to the lack ofeffectiveness in implementation of the policy include: Keywords : Effectiveness of Implementation, Highest Paid Retail Policy, SubsidizedFertilizer, Purchasing Power of Farmer.